Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 19



Work Step by Step

Combining like terms, the given expression simplifies to: $5x-7y-8x+3y$ =$5x-8x+3y-7y$ =$x(5-8)+y(3-7)$ =$-3x-4y$ We then substitute $x=9$ and $y=-8$ in the expression and simplify: $-3x-4y$ =$-3(9)-4(-8)$ =$-27+32$ =$5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.